Furniture Character [detail of larger Racquet Club Cottages Interior Scheme drawing] - Maurice Martiné::::::draftsman::: (1960)
Drawing of furniture design by Maurice Martiné, which is taken from a larger drawing with the identifier 007-3-c-38-06-01